2021
DOI: 10.3390/nu13093089
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Vitamin D Intake, Serum 25(OH)D3, 25(OH)D2 with Cognitive Performance in the Elderly

Abstract: Background: As life expectancy increases, cognitive performance decline in the elderly has become one of the major global challenges. We aimed to evaluate the association of dietary vitamin D (VD), serum 25-hydroxyvitamin D3 (25(OH)D3), 25-hydroxyvitamin D2 (25(OH)D2), and total 25-hydroxyvitamin (25(OH)D) concentration with cognitive performance in older Americans. Methods: The data from the National Health and Nutrition Examination Survey (NHANES), 2011–2014 was used. The cognitive performance was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Second, urinary 3-PBA has an estimated half-life of only 6-24 h [17][18][19][20], and thus may not be able to capture cumulative pyrethroid exposure in the human body. Third, we adjusted clinical factors such as BMI, hypertension, and diabetes, as potential confounders, as previous studies suggested [26,27]. However, we cannot rule out a possibility that those clinical factors may be potential causal intermediaries rather than confounding factors since they are the risk factor for cognitive impairment in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, urinary 3-PBA has an estimated half-life of only 6-24 h [17][18][19][20], and thus may not be able to capture cumulative pyrethroid exposure in the human body. Third, we adjusted clinical factors such as BMI, hypertension, and diabetes, as potential confounders, as previous studies suggested [26,27]. However, we cannot rule out a possibility that those clinical factors may be potential causal intermediaries rather than confounding factors since they are the risk factor for cognitive impairment in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Third, general health behaviors including physical activity and smoking pack-year were additionally considered. Last, physical status including body mass index (BMI) and presence of hypertension and diabetes were additionally considered as confounding variables [26,27]. Further, urinary creatinine concentration was considered as a potential confounder [28].…”
Section: Covariatesmentioning
confidence: 99%
“…According to the method used in the published literature ( 3 , 5 , 7 , 22 , 27 ), we further classified the scores according to three age stages. In each test, participants with scores below the minimum quartile for each age group were defined as having low poor cognitive performance.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function is associated with a variety of factors ( 1 , 2 ). Many previous studies have discussed the association between nutritional factors and cognition, such as vitamin D ( 3 , 4 ), zinc, copper, selenium ( 5 ), creatine ( 6 ), ω-3, and ω-6 fatty acids ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…As there is no recommended standard for cognitive impairment by CERAD-WL, CERAD-DR, AFT and DSST, the lowest quartile of these four scores was used as the cut-off points, which were adjusted according to age (Table 1) (27). Participants with scores lower than or equal to the cut-off points were defined as cognitive impairment.…”
Section: Cognitive Function Assessmentmentioning
confidence: 99%